ASSOCIATION BETWEEN ADMISSION BLOOD PRESSURE, INCIDENT CARDIOVASCULAR EVENTS AND EARLY MORTALITY IN PATIENTS WITH REVASCULARIZED CRITICAL LIMB ISCHEMIA. (June 2022) - Gaisset, Roxane; Lin, Franck; Lazareth, Isabelle; Mourad, Jean-Jacques; Priollet, Pascal; Emmerich, Joseph; Yannoutsos, Alexandra
Abstract : Objective: Patients with critical limb ischemia (CLI) present a high-risk of cardiovascular events and death. Hypertension is one of the most prevalent risk factors in this population. This study investigated the association between blood pressure (BP) level at hospital admission, major cardiovascular events (MACE) and one-year mortality in patients undergoing percutaneous revascularization for CLI. Design and method: This retrospective analysis of an ongoing cohort study included 285 consecutive patients ospitalised from November 2013 to December 2018. Major cardiovascular events, defined as heart failure, acute coronary syndrome, ischemic stroke and sudden death, were collected during the first year following revascularization. Multivariate analysis identified factors independently associated with MACE occurrence and one-year mortality. A p < = 0.05 was considered statistically significant. Results: The study included 157 men (55%) and 128 women (45%), mean age of 77.8 ± 12 years. Treated hypertension was present in 222 (78%) patients (admission systolic BP 132 (±18.2) mmHg, diastolic BP 69.9 (±7.79) mmHg, pulse pressure 62.3 (±15.8) mmHg and mean BP 90.7 (±9.77) mmHg); diabetes was present in 137 (48%) patients; 112 (39%) patients had known coronary heart disease (CHD) and 20 (7%) patients were dialysis dependent. During one-year follow-up after revascularization, 75 (26.3%) patients presented a MACE. Peri-operative mortality rate was 4% (12 patients, of whom 6 patients died from MACE). At one-year, cumulative mortality rate was 26.7% (76 patients) mostly from MACE. Twenty-three patients (8%) experienced major limb amputation. In multivariate analysis, the occurrence of MACE was associated with an increased mortality risk (HR 7.06 (2.99–17.51), p<0.001). Of the four BP indexes, systolic BP (p = 0.01), mean BP (p = 0.02), pulse pressure (p = 0.02), but not diastolic BP, were significantly and inversely correlated with 1-year mortality. Decompensated heart failure and CHD were both associated with incident MACE in multivariate analysis, independently of confounders. Conclusions: Incident MACE were prevalent in the year following endovascular procedure in patients with CLI and were associated with an increased risk of mortality. There is an inverse association between admission BP and one-year mortality, independently of the occurrence of MACE. Decompensated heart failure and CHD are important contributors for the occurrence of MACE.